Potential of acylated peptides to target the influenza A virus - Lauster, Daniel; Pawolski, Damian; Storm, Julian; Ludwig, Kai; Volkmer, Rudolf; Memczak, Henry; Herrmann, Andreas; Bhatia, Sumati (Beilstein Journal of Organic Chemistry, 2015)
For antiviral drug design, especially in the field of influenza virus research, potent multivalent inhibitors raise high expectations for combating epidemics and pandemics. Among a large variety of covalent and non-covalent scaffold systems for a multivalent display of inhibitors, we created a simple supramolecular platform to enhance the antiviral effect of our recently developed antiviral Peptide B (PeBGF), preventing binding of influenza virus to the host cell. By conjugating the peptide with stearic acid to create a higher-order structure with a multivalent display, we could significantly enhance the inhibitory effect against the serotypes of both human pathogenic influenza virus A/Aichi/2/1968 H3N2, and avian pathogenic A/FPV/Rostock/34 H7N1 in the hemagglutination inhibition assay. Further, the inhibitory potential of stearylated PeBGF (C18-PeBGF) was investigated by infection inhibition assays, in which we achieved low micromolar inhibition constants against both viral strains. In addition, we compared C18-PeBGF to other published amphiphilic peptide inhibitors, such as the stearylated sugar receptor mimicking peptide (Matsubara et al. 2010), and the “Entry Blocker” (EB) (Jones et al. 2006), with respect to their antiviral activity against infection by Influenza A Virus (IAV) H3N2. However, while this strategy seems at a first glance promising, the native situation is quite different from our experimental model settings. First, we found a strong potential of those peptides to form large amyloid-like supramolecular assemblies. Second, in vivo, the large excess of cell surface membranes provides an unspecific target for the stearylated peptides. We show that acylated peptides insert into the lipid phase of such membranes. Eventually, our study reveals serious limitations of this type of self-assembling IAV inhibitors.
Keywords: amphiphilic peptide; antiviral; influenza virus; multivalency; self-assembled structures

(untitled) - Kuiken, T.; Riteau, B.; Fouchier, R. A. M.; Rimmelzwaan, G. F. (Curr. Opin. Virol., 2012)

(untitled) - van der Vries, E.; Schutten, M.; Fraaij, P.; Boucher, C.; Osterhaus, A. (Adv. Pharmacol., 2013)

(untitled) - Vanderlinden, E.; Naesens, L. (Med. Res. Rev., 2014)

(untitled) - Papp, I.; Sieben, C.; Ludwig, K.; Roskamp, M.; Böttcher, C.; Schlecht, S.; Herrmann, A.; Haag, R. (Small, 2010)

(untitled) - Papp, I.; Sieben, C.; Sisson, A. L.; Herrmann, A.; Haag, R. (J. Controlled Release, 2010)

(untitled) - Papp, I.; Sieben, C.; Sisson, A. L.; Kostka, J.; Böttcher, C.; Ludwig, K.; Herrmann, A.; Haag, R. (ChemBioChem, 2011)

(untitled) - Tuzikov, A. B.; Chinarev, A. A.; Gambaryan, A. S.; Oleinikov, V. A.; Klinov, D. V.; Matsko, N. B.; Kadykov, V. A.; Ermishov, M. A.; Demin, I. V.; Demin, V. V.; Rye, P. D.; Bovin, N. V. (ChemBioChem, 2003)

(untitled) - Lees, W. J.; Spaltenstein, A.; Kingery-Wood, J. E.; Whitesides, G. M. (J. Med. Chem., 1994)

(untitled) - Mammen, M.; Dahmann, G.; Whitesides, G. M. (J. Med. Chem., 1995)

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Matsubara, T.; Sumi, M.; Kubota, H.; Taki, T.; Okahata, Y.; Sato, T. (J. Med. Chem., 2009)

(untitled) - Matsubara, T.; Onishi, A.; Saito, T.; Shimada, A.; Inoue, H.; Taki, T.; Nagata, K.; Okahata, Y.; Sato, T. (J. Med. Chem., 2010)

(untitled) - Jones, J. C.; Turpin, E. A.; Bultmann, H.; Brandt, C. R.; Schultz-Cherry, S. (J. Virol., 2006)

(untitled) - Jones, J. C.; Settles, E. W.; Brandt, C. R.; Schultz-Cherry, S. (Vaccine, 2011)

(untitled) - Jones, J. C.; Settles, E. W.; Brandt, C. R.; Schultz-Cherry, S. (Antimicrob. Agents Chemother., 2011)

(untitled) - Carpino, L. A.; Sadat-Aalaee, D.; Chao, H. G.; DeSelms, R. H. (J. Am. Chem. Soc., 1990)

(untitled) - Tu, R. S.; Tirrell, M. (Adv. Drug Delivery Rev., 2004)

Eur. Pat. Appl. - Memczak, H.; Stöcklein, W.; Ehrentreich-Förster, E. (Peptides for binding of influenza viruses and inhibition of influenza infections, 2014)

(untitled) - Cui, H.; Webber, M. J.; Stupp, S. I. (Biopolymers, 2010)

(untitled) - Cavalli, S.; Albericio, F.; Kros, A. (Chem. Soc. Rev., 2010)

(untitled) - Hirst, G. K. (J. Exp. Med., 1942)